Validation of St. George's Respiratory Questionnaire (SGRQ) in Chronic Obstructive Pulmonary Disease (COPD) at Respira Lung Hospital Yogyakarta - P.D. Pratiwi; Dyah Aryani Perwitasari (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The prevalence of COPD in Indonesia is increasing. Over the world, COPD is predicted to be the third cause of death in 2020. As the chronic disease, quality of life became one of the outcome treatments of COPD. This research was aimed to validate Indonesian version of St. George's Respiratory Questionnaire (SGRQ) Indonesia. This study used cross sectional design approach from June to July 2016, conducted at Respira Lung Hospital, Yogyakarta. Data was collected from medical record and direct interviews to patients using SGRQ. An inclusion criterion was adult patients with COPD. Some statistical tests were performed to analyze construct validity, known group validity and reliability of Indonesian version of SGRQ. We recruited 41 respondents. The SGRQ meet reliability criteria with the value of Cronbach alpha are > 0.7 for symptom, activity and impact domains. There are 17 questions and 10 questions in symptom, activity and impact domains which do not meet convergent and discriminant validity. The significant difference is found in symptom domain for the 17-48 and 49-80 year age. The SGRQ Indonesian version is not valid enough to be used in clinical practice but still reliable.